2021
DOI: 10.1038/s41467-021-24652-1
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of regulation of bacterial capsule assembly by Wzc

Abstract: Bacterial extracellular polysaccharides (EPSs) play critical roles in virulence. Many bacteria assemble EPSs via a multi-protein “Wzx-Wzy” system, involving glycan polymerization at the outer face of the cytoplasmic/inner membrane. Gram-negative species couple polymerization with translocation across the periplasm and outer membrane and the master regulator of the system is the tyrosine autokinase, Wzc. This near atomic cryo-EM structure of dephosphorylated Wzc from E. coli shows an octameric assembly with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 52 publications
0
72
0
Order By: Relevance
“…We have previously demonstrated the unique conformational dynamics of the catalytic core of the archetypal BY-kinase, Escherichia coli (K12) Wzc (Wzc CDΔC ); these dynamics appear to have significant functional consequences. Our studies revealed the presence of two major conformations with distinct long-and short-range structural features (Hajredini et al, 2020) 2+ , is stabilized upon formation of a closed octameric ring seen both in the structure of the isolated CD (Bechet et al, 2010) as well as in the membrane-anchored full-length protein (Yang et al, 2021). Oligomer formation is necessary to enable intermolecular autophosphorylation.…”
Section: Introductionmentioning
confidence: 78%
“…We have previously demonstrated the unique conformational dynamics of the catalytic core of the archetypal BY-kinase, Escherichia coli (K12) Wzc (Wzc CDΔC ); these dynamics appear to have significant functional consequences. Our studies revealed the presence of two major conformations with distinct long-and short-range structural features (Hajredini et al, 2020) 2+ , is stabilized upon formation of a closed octameric ring seen both in the structure of the isolated CD (Bechet et al, 2010) as well as in the membrane-anchored full-length protein (Yang et al, 2021). Oligomer formation is necessary to enable intermolecular autophosphorylation.…”
Section: Introductionmentioning
confidence: 78%
“…as per a previous report (Sande et al, 2019). have been provided as per the PDB files 2J58 (Dong et al, 2006) and 7NII (Yang et al, 2021) (respectively) for size references. Structure models for WzaB (Fig.…”
Section: Competing Interests 927mentioning
confidence: 99%
“…All proteins, spaces, and distances have been depicted at the same relative scale across a representative 327 Å periplasmic space in a M. xanthus cell. X-ray crystal structures for Wza Ec (chain A) and Wzc Ec (chains F and G) have been provided as per the PDB files 2J58 (Dong et al ., 2006) and 7NII (Yang et al ., 2021) (respectively) for size references. Structure models for WzaB (Fig.…”
Section: Supplementary Figure S1mentioning
confidence: 99%
See 1 more Smart Citation
“…Wzc autophosphorylation causes octamer dissociation leading to closure of the Wza translocon. Reactivation then depends on the dephosphorylation of Wzc by Wzb [ 21 ]. Detailed mechanistic studies have not been performed in P. gingivalis ; however, deletion of the ptk1 gene results in loss of EPS secretion in strain 33277, and failure to produce a capsule in strain W83 [ 15 ].…”
Section: Tyrosine Kinase and Phosphatase Functions In P Gin...mentioning
confidence: 99%